Membrane raft-mediated regulation of glucose signaling pathway leading to acrosome reaction in chicken sperm†. Issue 6 (4th February 2019) - Ushiyama, Ai; Priyadarshana, Chathura; Setiawan, Rangga; Miyazaki, Hitoshi; Ishikawa, Naoto; Tajima, Atsushi; Asano, Atsushi
Abstract: Despite knowledge that glucose metabolism is essential for the regulation of signaling cascades in the sperm that are pre-assembled into specific areas and function at multistage for fertilization, the physiological roles of glucose in avian sperm are poorly understood. Accumulated results of studies conducted in our laboratory and others indicate that sperm possess membrane microdomains, or membrane rafts, which play important roles in several processes, including the induction of acrosome reaction (AR). When characterizing proteomes associated with chicken sperm rafts, we observed marked enrichment of glucose transporter 3 (GLUT3). Here we show that glucose uptake is mediated by membrane rafts and stimulates AR induction by activating AMP-activated protein kinase (AMPK). Using a specific antibody, we observed that GLUT3 is localized to the entire flagellum and acrosome region and highly associated with membrane rafts. The addition of glucose stimulated AR in a dose-dependent manner without affecting sperm motility. AR and glucose uptake assays were performed using both inhibitors and activators, and demonstrated that glucose-dependent AR results from the activity of a glucose transporter located in membrane rafts and associated with AMPK. To better understand the mechanism of AMPK activation by glucose, we evaluated localization and phosphorylation status of AMPKα, showing that glucose uptake stimulates AMPKα phosphorylation, leading to its complete activation. Together, these results lead us to propose a novel mechanism by which glucose uptake stimulates the AMPK signaling pathway via membrane rafts, resulting in maximal acrosomal responsiveness in avian sperm as migrating upward to a fertilization site. Abstract : Glucose uptake is mediated by membrane rafts, which results in stimulation of AR induction via AMP-activated protein kinase (AMPK) activation.